Modulation of Trp Channels by N-Glycosylation and Phosphorylation - Madrid-Montecinos, R; Pertusa-Pastor, M (Springer International Publishing, 2015)
Transient receptor potential (TRP) are cation permeable channels found in eukaryotic organisms, from yeast to human. These channels are involved in several physiological processes ranging from Ca2+ and Mg2+ homeostasis to sensory functions, including vision, pheromone signalling, taste, nociception, mechanotransduction and temperature sensing, among others. Most of these channels show covalent post-translational modifications (PTMs) that have a profound effect on their physiological function, by influencing their subcellular trafficking and/or their biophysical properties. Among these modifications, N-linked glycosylation and phosphorylation are two of the most relevant PTMs determining the functional expression of TRP channels. In this chapter we summarize their role in modulating the functional properties of TRP channels, with a critical role in sensory transduction. © Springer International Publishing Switzerland 2016. All rights reserved.